Cluster Frontline Demonstrations (CFLDs): An effective approach to increase the productivity of mustard in arid zone of Gujarat - Traloki Singh; Arvind Singh Tetarwal (Annals of Agricultural Research, 2022)
A field experiment was carried out by the ICAR-CAZRI, Krishi Vigyan Kendra, Bhuj-Kachchh at farmers field, it was investigated the effect of cluster frontline demonstrations (CFLDs) on mustard productivity during Rabi, 2016-17 to 2020-21. During this period, a total of 243 CFLDs on Integrated Crop Management (ICM) in mustard with high yielding variety of mustard (GDM-4) with full package and practices were undertaken in 106 ha area with 14 villages in Bhuj, Nakhatrana, Anjar, Rapar, and Bhachau talukas of Kachchh district. High yielding variety of mustard (GDM-4 is resistance to white rust and Alternaria blight) with improved package of practices displayed in demonstration plots, while existing technology treated as farmer’s practice or local check. Based on five years of data, the improved practice (IP) had an average seed output of 2171 kg ha-1, which enhance output upto 18.17% from the farmer’s practice about 1865 kg ha-1. The demonstrated technology, the average extension gap, technology gap and technology index were 306.4 kg ha-1, 327.6 kg ha-1, and 13.11%, respectively. The economics of demonstrations revealed, the viability of enhanced technology, with a net return of 61875 Rs. ha-1 and a benefit-cost ratio (BCR) of 3.09, compared to 49032 Rs. ha-1 and 2.75 for conventional technology. A wide range of extension and technology gaps had a detrimental influence on crop output and net return in general. The results revealed that the adoption of high yielding variety with full package of practices increased mustard productivity with a significant reduction in extension and technology gap.